Analisis Pengaturan Layout Gudang Sparepart Menggunakan Metode Dedicated Storage di Gudang Bengkel Yamaha Era Motor - Imelda Agustina; Resista Vikaliana (Research Center and Case Clearing House PPM School of Management, 2021)
Era Motor Tambun Yamaha Dealer was a company running in field of sales of various types of Yamaha motorcycles. The problems frequently faced by warehouses were the great number of parts not accommodated in the slots, same types of parts placed in more than one location, and the absence of permanent storage location, so employees frequently faced difficulties in finding required parts. The study aimed to provide spare-part layout improvement. The parts stored would be placed in permanent locations to expedite the process of storage and taking of parts from the warehouse by maintaining the existing warehouse area using Dedicated Storage method so the use of storage area in the warehouse became more optimal. The placement was based on comparison of activities of each part with spatial requirement needed by the parts. Therefore, how much actually was the area needed by spare-part warehouse could be found out. With the design of new blocks using dedicated storage methods, it was expected to minimize that the parts could occupy permanent locations to facilitate the employees in storing and taking the parts, so the in-and-out flow of parts became smooth. Furthermore, from the result of the study, it could be concluded that the amount of ratio of block area increased into 88.8% from current block area that was only 55.5%. Besides that, it also obtained the design of new blocks with size of 10x2x3 meters and layout design with total used floor area of 176 meters with total mileage of 50 meters/day..